Postprandial plasma carotenoid responses following consumption of strawberries, red wine, vitamin C or spinach by elderly women - Paiva, Sergio Alberto Rupp de [UNESP]; Yeum, Kyung-Jin; Cao, Guohua; Prior, Ronald L.; Russell, Robert M. (My University, 1998)
This study investigated the postprandial plasma responses of carotenoids for 24 h after feeding five specific breakfast beverages; four of which had low or no carotenoid content. In seven fasting healthy elderly female subjects a blood sample (baseline) was obtained, after which they were given a breakfast beverage, containing one of the following: 1) strawberries (240 g); 2) ascorbic acid (1250 mg); 3) spinach (294 g); 4) red wine (300 mL); and 5) control (breakfast beverage only). Blood samples were collected at 0.5, 1, 4, 7, 11, 15 and 24 h. Plasma carotenoids were measured using HPLC. No significant differences were found in the levels of the plasma carotenoids measured among the various treatments at baseline. In the spinach treatment, plasma lutein, zeaxanthin and β-carotene levels at 7, 11, 15 and 24 h were significantly higher than those at baseline, as expected. All of the carotenoids measured in the control and vitamin C treatments, at subsequent sampling times were not significantly different from those at baseline. However, for most carotenoids, strawberry and red wine feeding resulted in significantly lower carotenoids values from baseline at 11 and 15 h. Subjects who received a diet with low levels of carotenoids, but whose postprandial plasma levels of carotenoids remain steady, might be explained by a mechanism that promotes secretion of carotenoids into the circulation. Assuming that plasma carotenoids are being used over time, we hypothesize that strawberries and red wine contain some substances that interfere with the secretion of carotenoids into the circulation.
Keywords: Carotenoids; Fruits; Humans; Postprandial; Red wine; Vegetables; antioxidant; ascorbic acid; carotenoid; aged; aging; antioxidant activity; cancer prevention; cardiovascular disease; clinical article; controlled study; dietary intake; female; fruit; human; spinach; vegetable; vitamin intake; wine; Aged; Analysis of Variance; Ascorbic Acid; Cholesterol, LDL; Chromatography, High Pressure Liquid; Diet; Female; Fruit; Postprandial Period; Wine; Fragaria x ananassa; Spinacia oleracea